TIMELINESS OF FINANCIAL REPORTS AFFECTED BY INFORMATION TECHNOLOGY WITH THE QUALITY OF HUMAN RESOURCES AS A MODERATION VARIABLE - Desi Permata Sari; Witra Maison; Siska Yulia Defitria (Jurnal Ekonomi, 2023)
This study aims to look at the effect of information technology on the timeliness of financial reporting with the quality of human resources as a moderating variable in regency/city Bawaslu in West Sumatra. In this study the method used is the sampling technique, namely Total Sampling by distributing questionnaires. The variables in this study were information technology as the independent variable, timeliness of reporting as the dependent variable and the quality of human resources as the moderating variable. The analytical method used in this study is associative quantitative and Moderated Regression Analysis (MRA). The results of this study indicate that information technology has a positive effect on the timeliness of financial reporting, while the quality of human resources can strengthen the relationship between information technology and the timeliness of financial reporting.